Archives and Justice: Willard Ireland’s Contribution to the Changing Legal Framework of Aboriginal Rights in Canada, 1963–1973 - Lindsay, Anne (Archivaria, 2011)
Despite their pivotal roles in collecting, organizing, preserving, and disseminating important cultural and legal records, the contributions of Canadian archivists to the pursuit of human rights and social justice in Canada and the world have often been overlooked. Yet these contributions have shaped the public and legal discourse about such issues as Indigenous rights, and have echoed in the court decisions that form the basis of our understandings of these issues today. Because of their access to information about the deeper historical context and archival history of records, archivists often have unique insights to offer; this access to critical context and history, however, often seems taken for granted. The life and career of Willard Ernest Ireland (1914–1979), British Columbia’s Provincial Archivist from 1940 to 1974, is an example of this oversight. Little has been written about Ireland and the influence of his career not just in preserving history but also in actually making it. This paper will examine Ireland’s key contributions to two twentieth-century legal cases, Regina v. White and Bob and Calder v. The Attorney General of British Columbia, cases that were critical in establishing the legal basis for Indigenous rights in Canada. RÉSUMÉ Malgré leur rôle essentiel dans l’acquisition, le classement, la préservation et la diffusion de documents culturels et légaux importants, les contributions des archivistes canadiens en matière de droits humains et de justice sociale au Canada et dans le monde ont souvent été négligées. Pourtant, ces contributions ont influencé le discours public et légal par rapport aux questions telles les droits des Autochtones et elles ont résonné dans les décisions judiciaires qui sont aujourd’hui à la base de notre connaissance de ces questions. Étant donné leur accès à une information plus poussée du contexte historique et de l’histoire des documents d’archives, les archivistes apportent souvent des perspectives uniques; cependant, on prend souvent pour acquis cet accès au contexte et à l’histoire. La vie et la carrière de Willard Ernest Ireland (1914- 1979), archiviste provincial de la ColombieBritannique de 1940 à 1974, illustre bien cet oubli. On a peu écrit au sujet d’Ireland et de l’influence de sa carrière, non seulement sur la préservation de l’histoire, mais aussi sur la création même de celle-ci. Ce texte examinera les contributions clés de Ireland à deux causes judiciaires, Regina v. White and Bob et Calder v. The Attorney General of British Columbia, causes critiques pour l’établissement d’un fondement légal pour les droits des Autochtones au Canada.